2013 Kansas Performance Tests with Winter Wheat Varieties - Lingenfelser, Jane (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2015)
The Kansas Agricultural Experiment Station annually compares both new and currently grown varieties in the state’s major crop-producing areas. These performance tests generate unbiased performance information designed to help Kansas growers select wheat varieties suited for their area and conditions. Contributors Main Station, Manhattan Jane Lingenfelser, Assistant Agronomist (Senior Author) Bill Bockus, Plant Pathologist Erick DeWolf, Extension Plant Pathologist Allan Fritz, Wheat Breeder Mary Knapp, Weather Data Librarian Jeff Whitworth, Extension Entomologist Experiment Fields Eric Adee, Ottawa Gary Cramer, Hutchinson James Kimball, Ottawa Randall Nelson, Scandia Research Centers Patrick Evans, Colby Kelly Kusel, Parsons Alan Schlegel, Tribune Clayton Seaman, Hays Monty Spangler, Garden City Gurong Zhang, Hays Others Ming Chen, USDA Richard Chen, Laura McLaughlin, USDA Justin Knopf, Gypsum, KS Rebecca Miller, Grain Science and Industry Jim Shroyer, Agronomy
Keywords: Wheat; Crop development; Diseases; Weather; Insects; Statistics; Kansas